ЎЗБЕК ТИЛИ ДАРСЛАРИДА АРАЛАШ ТАЪЛИМ УЧУН ЎҚУВ КОНТЕНТИНИ ЯРАТИШ ВА ФОЙДАЛАНИШНИНГ ЎЗИГА ХОСЛИГИ ҲАҚИДА - Юлдашева, Ш.Ш.; Юсупова, Г.А. (SCIENCE and SOCIETY, 2019)
The article discusses the principles, stages, and methods of organizing Uzbek language classes on a mixed basis. The peculiarities of creating and using Uzbek language content for mixed education are explored in some of the issues of integrating traditional education and e-learning. The conclusion provides an overview of the challenges of implementing a mixed education approach and outlines the ways in which this education can be effectively developed.
Keywords: blended learning; Uzbek language; digital technologies; interactive exercises; interactive dictator; "Savodxon"